Endothelial Immunity Trained by Coronavirus Infections, DAMP Stimulations and Regulated by Anti-Oxidant NRF2 May Contribute to Inflammations, Myelopoiesis, COVID-19 Cytokine Storms and Thromboembolism - Shao, Ying; Saredy, Jason; Xu, Keman; Sun, Yu; Saaoud, Fatma; Drummer, Charles; Lu, Yifan; Luo, Jin J.; Lopez-Pastrana, Jahaira; Choi, Eric T.; Jiang, Xiaohua; Wang, Hong; et al. (Frontiers in Immunology, 2021)
To characterize transcriptomic changes in endothelial cells (ECs) infected by coronaviruses, and stimulated by DAMPs, the expressions of 1311 innate immune regulatomic genes (IGs) were examined in 28 EC microarray datasets with 7 monocyte datasets as controls. We made the following findings: The majority of IGs are upregulated in the first 12 hours post-infection (PI), and maintained until 48 hours PI in human microvascular EC infected by middle east respiratory syndrome-coronavirus (MERS-CoV) (an EC model for COVID-19). The expressions of IGs are modulated in 21 human EC transcriptomic datasets by various PAMPs/DAMPs, including LPS, LPC, shear stress, hyperlipidemia and oxLDL. Upregulation of many IGs such as nucleic acid sensors are shared between ECs infected by MERS-CoV and those stimulated by PAMPs and DAMPs. Human heart EC and mouse aortic EC express all four types of coronavirus receptors such as ANPEP, CEACAM1, ACE2, DPP4 and virus entry facilitator TMPRSS2 (heart EC); most of coronavirus replication-transcription protein complexes are expressed in HMEC, which contribute to viremia, thromboembolism, and cardiovascular comorbidities of COVID-19. Since ECs have novel trained immunity (TI), in which subsequent inflammation is enhanced. Upregulated proinflammatory cytokines such as TNF, IL6, CSF1 and CSF3 and TI marker IL-32 as well as TI metabolic enzymes and epigenetic enzymes indicate TI function in HMEC infected by MERS-CoV, which may drive cytokine storms. Upregulated CSF1 and CSF3 demonstrate a novel function of ECs in promoting myelopoiesis. Mechanistically, the ER stress and ROS, together with decreased mitochondrial OXPHOS complexes, facilitate a proinflammatory response and TI. Additionally, an increase of the regulators of mitotic catastrophe cell death, apoptosis, ferroptosis, inflammasomes-driven pyroptosis in ECs infected with MERS-CoV and the upregulation of pro-thrombogenic factors increase thromboembolism potential. Finally, NRF2-suppressed ROS regulate innate immune responses, TI, thrombosis, EC inflammation and death. These transcriptomic results provide novel insights on the roles of ECs in coronavirus infections such as COVID-19, cardiovascular diseases (CVD), inflammation, transplantation, autoimmune disease and cancers.